Podophyllotoxin Exposure Causes Spindle Defects and DNA Damage-Induced Apoptosis in Mouse Fertilized Oocytes and Early Embryos - Hu, Lin-Lin; Liao, Bi-Yun; Wei, Jing-Xi; Ling, Yan-Lan; Wei, Yu-Xia; Liu, Zhong-Lin; Luo, Xiao-Qiong; Wang, Jun-Li (Frontiers in Cell and Developmental Biology, 2020)
Podophyllotoxin (PPT) is a kind of lignans extracted from the roots and stems of the genus Podophyllum from the tiller family, and it has been widely used in the treatment of condyloma acuminatum, multiple superficial epithelioma in the clinics. However, PPT has been reported to be toxic and can cause liver defects and other organ poisoning. In addition, emerging evidences also indicate that PPT has reproductive toxicity and causes female reproduction disorders. In this study, we used fertilized oocytes and tried to explore the effects of PPT on the early embryonic development with the mouse model. The results showed that exposure to PPT had negative effects on the cleavage of zygotes. Further analysis indicated that PPT could disrupt the organization of spindle and chromosome arrangement at the metaphase of first cleavage. We also found that PPT exposure to the zygotes induced excessive reactive oxygen species (ROS), suggesting the occurrence of oxidative stress. Moreover, in the PPT-exposed embryos, there was positive γH2A.X and Annexin-V signals, indicating that PPT induced embryonic DNA damage and early apoptosis. In conclusion, our results suggested that PPT could affect spindle formation and chromosome alignment during the first cleavage of mouse embryos, and its exposure induced DNA damage-mediated oxidative stress which eventually led to embryonic apoptosis, indicating the toxic effects of PPT on the early embryo development.